Experimental Study of Sediment Transport in Meandering Channels - Yilmaz, Levent (Springer Science and Business Media LLC, 2007)
Sediment transport in a meandering channel is measured in a laboratory flume. The measurements are evaluated and compared with previous studies. The values of the calculated sediment transport rates using previous formulas are generally overestimated. Under these circumstances, in this research, it is noticed that the sediment transport rates as measured in the laboratory, and sediment transport capacities computed with the Einstein’s approach, behave in a quite similar way, seemingly closely related to the varying bottom shear velocity or stress. Einstein’s approach for bed load comparison is chosen in this experimental research because it has been tested to some extent.